2013
DOI: 10.1007/s10493-013-9656-z
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro activities of plant extracts from the Brazilian Cerrado and Pantanal against Rhipicephalus (Boophilus) microplus (Acari: Ixodidae)

Abstract: A total of 73 ethanol extracts from different anatomical parts of 44 plant species belonging to 24 families, native to the Mid-Western region of Brazil, were assessed in vitro for their effect on the reproductive cycle of engorged females of the cattle tick Rhipicephalus (Boophilus) microplus, using the adult immersion test. All extracts were evaluated at the concentration of 0.2 % and, among the extracts tested, the one obtained from the fruits of Guarea kunthiana (Meliaceae) proved to be highly efficacious, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
1
11
0
1
Order By: Relevance
“…Therefore, we believe it should be better studied at the histological level. Our results are close to those of Barbosa et al (2013), in which ethanol extract of O. lancifolia (Schott) Mez leaves and bark at 2 mg/mL showed significant activity on the reproductive parameters of R. (B.)…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, we believe it should be better studied at the histological level. Our results are close to those of Barbosa et al (2013), in which ethanol extract of O. lancifolia (Schott) Mez leaves and bark at 2 mg/mL showed significant activity on the reproductive parameters of R. (B.)…”
Section: Discussionsupporting
confidence: 88%
“…(B.) microplus engorged females and larvae (Barbosa et al 2013;Santos et al, 2013). Likewise, Conceição et al (2017) evaluated hexane, ethyl acetate and ethanol extracts of Ocotea acidophyla leaves and all of them demonstrated acaricidal activity against different stages of the cattle tick.…”
Section: Introductionmentioning
confidence: 99%
“…Vasconcelos et al (2014) reported that all the syringe contents were counted under a stereoscopic microscope. On the other hand, Barbosa et al (2013) reported that when less than 50% of the larvae hatched, eggs and larvae were mixed in 4 mL of a 1:1 solution of aqueous ethanol at 96% and glycerin. Then larvae and eggs were counted in 1 mL of the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Os ovos dos grupos II e III apresentaram um aspecto ressecado e coloração escura. Barbosa et al (2013) fizeram a mesma observação dos ovos de R. microplus tratados com o extrato de Guarea kunthiana. É possível que o extrato de N. tabacum tenha removido a cera de revestimento que protege os ovos contra a desidratação, o que possibilitou a troca osmótica dos ovos com o meio, e consequentemente o aparecimento desse aspecto ressecado e enrugado (Politi et al, 2015).…”
Section: Resultsunclassified